A Rare Case of Cholangiocellular Liver Cancer with Hematogenous Metastases and Organ Changes in the Generalization of the Process - O. V. Vorobeva (Креативная хирургия и онкология, 2022)
Introduction. Cholangiocellular cancer is a malignant tumor from the epithelium of the bile ducts. Intravital diagnosis is often difficult to make due to the absence of any definitive signs of cancer and problems with detecting the first signs. Following the relevance of the problem, a case of cholangiocellular liver cancer with generalized metastases is presented.Materials and methods. The analysis of the received supporting medical documentation and the description of macroand micropreparations using histological (hematoxylin and eosin staining) and immunohistochemical methods were carried out.Results and discussion. Patient L.M., 60 years old, died at home, was referred by a general practitioner to the pathology department for autopsy examination. During the forensic autopsy, the macroscopic examination revealed dense liver substance, a «tree-like» mass of gray-yellow-brown color on the sections around the portal vein and intrahepatic bile ducts, with involvement of the right and left liver lobes and multiple gray nodules located throughout the liver parenchyma. The intrahepatic bile ducts malfunction due to expanding tumor tissue. Histological examination revealed a moderately differentiated tumor growth of cholangiocellular carcinoma, consisting of polymorphic cells separated by layers of fibrous tissue with areas of necrosis, foci of cholestasis. Immunohistochemical analysis of the tumor tissue of the lungs, liver: cytokeratins CAM 5.2 (+). All groups of lymph nodes of hepatoduodenal ligament, along vesicular and common bile ducts, hepatic artery and portal vein, surrounding left gastric and common hepatic artery, as well as lymph nodes of posterior pancreaticoduodenal group and distant lymph nodes are celiac; upper mesenteric and paraaortic zones appear unremarkable. Cerebral edema, pulmonary edema and necronephrosis were reported.Conclusion. The presented case is of particular interest to practitioners owing to the absence of the characteristic lymph node metastases and presence of hematogenous metastases and development of multiple organ failure.